Counselling and training on making processed pudding and juice from Siamese pumpkin to reduce high blood pressure - Syahrir, Sukfitrianty; Nurul, Nurul; Rahman, Nur Fadhilah; Amelia, Fitria (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Hypertension is a major risk factor for death. People with hypertension continue to increase from year to year in various ages caused by various factors that affect the incidence of hypertension due to lifestyle and low potassium intake. The potassium content in chayote is known to have a diuretic effect so that it can reduce salt levels in the blood through urinary excretion. If left untreated it can affect all organ systems and can arise other diseases such as atherosclerotic cardiovascular disease, heart failure, stroke, and kidney failure. The type of service used is descriptive approach service that aims to educate and train the community on how to process and the benefits of chayote to reduce high blood pressure. The entire service population is people living in Halahalaya Hamlet, Kanreapia Village, Tombolo Pao District, Gowa Regency, totaling 30 respondents. The methods carried out in this program are counselling and demonstration. From the results of data analysis, it is known that there was an increase in knowledge before counselling was given and after counselling was given with an average value of 49.33 before counselling, then increased to 64.67 after counselling. The community needs to utilize existing assets such as the processing of chayote as a traditional medicine that can reduce hypertension.